PERANCANGAN STRATEGI KREATIF REBRANDING PROGRAM SARJANA SISTEM INFORMASI DENGAN MENGGUNAKAN METODE ADDIE - Deli Deli; Hendy (Universitas Widyatama, 2021)
Brand identity is a unique characteristic of a brand. Brand identity can be seen in the form of symbols, visuals, and physical representations that serve to make it easier for consumers to recognize a brand. Over the time, brand identity has become much more important and noticed. Therefore there is a demand for a brand to make changes. These changes were made to defend against extreme market developments. This process is known as rebranding, which will produce a reconstructed brand identity to compete in a new market. Corporate rebranding has become a common practice to adapt to changes in the micro and macro environment. With the increasing number of successful organizations after implementing corporate rebranding, it creates interest in the academic world, especially in universities. Therefore, the author emphasizes this application study to raise the topic of